UVEITIS RELATED FACTORS IN PATIENTS WITH SPONDYLOARTHRITIS - Bilge, Nazife Sule Yasar; Kasifoglu, Timucin; Kiraz, Sedat; Ertenli, Ali Ihsan; Kucuksahin, Orhan; Dalkilic, Ediz; Kalyoncu, Umut (Bmj Publishing Group, 2019)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 12-15, 2019 -- Madrid, SPAIN